STRATEGI PEMASARAN BEPANG MENGGUNAKAN KOMBINASI METODE SWOT AHP DI INDUSTRI BEPANG UD. CAP BUNGA - Rizki Amalia; Nina Hairiyah (Jurnal Teknologi Agro-Industri, 2019)
Trade (UD) Cap Bunga an industry houselhold products unlike bepang located in pelaihari sout Kalimantan. Research purpose analyze what factors most affect planning marketing strategies bepang internally and externally. Determine marketing strategies bepang uses the training ahp by the application of expert choice 2000. Methods used is the methods of Analysis Strengh, Weaknes, Opportunities, Threat ( SWOT) and Anaytic Hirerarchy Proces (AHP). The results of marketing strategies factors influencing the bepang is. Power (Strengh) bepang products quality product using the resulting 4,66 and industry bepang obtain certificates/business licensing letter 4,33 produced by the. Weaknes (weaknes) bepang use simple product packaging and the products of the 2,66 bepang not easlily repaired by 1,66 score.Opportunities (opportunities) product bepang easy marketed the score by which produced 4,66 and products bepang competitive with other products the score the was produced 4,66.Threat (threat) in marketing not promote a printing press and electronic media the score that was produced 2,66 and is a product similar with score that was produced 3. Alternative marketing strategy using the method of analysis of SWOT AHP is to maintain quality material so that the certificate/letter of bussiness permission to make bepang product UD. Cap Bunga easy to market and qualite competitive with ather products.